Milk peptide induced miRNA-369 facilitates bone functions in the rat osteoblasts - KAUR, TARUNEET; UPADHYAY, DIVYA; VIJ, RISHIKA; KAPILA, RAJEEV; KAPILA, SUMAN (The Indian Journal of Animal Sciences, 2021)
The animal’s health and productivity is chiefly influenced by its anatomy and physiology. Moreover, bone growth in animals is also associated to overall health and production. Besides, bone fractures accounts to constrained food intake, reduced immune function and general productivity losses. In poultry animals, bone deformities, renders severe costs in the meat production and egg quality. The treatment for various bone related issues is both time and capital seeking. Besides, currently available therapies, i.e. bisphosphonates, raloxifene are associated with various side effects like jaw osteonecrosis, vaginal bleeding etc. The present study reports the bone promoting effect in milk peptide induced miRNA, miR369. Findings represents an enhanced bone proliferation and differentiation under the influence of miR369 in in vitro rat osteoblasts culture. The bone marker enzyme alkaline phosphatase and osteoblast specific protein expression were tested using ELISA. miR369 significantly stimulated the marker protein levels. Additionally, miR369 when injected to neonatal rat pups, showed improved osteoblast marker gene(s) expression. The study demonstrates the positive role of miR369 in the bone functions and hence, advocates its functional utility for the management of various bone ailments prevailing in animals and/or humans. Besides miR369, a putative molecular gene therapeutic agent can prove revolutionary in controlling the animal health losses ascribed to deteriorating bone health.